A Comparative Study of The Phenomenon of “Party Switching” In The Political Systems of Indonesia and Brazil: Studi Komparatif Fenomena "Party Switching" dalam Sistem Politik Indonesia dan Brasil - Risyah Aprimayanti; Jusmalia Oktaviani; Noer Apptika Fujilestari (Jurnal Pemerintahan dan Politik, 2026)
Purpose : This study compares the factors driving “party switching” in the political systems of Indonesia and Brazil. Design/methodology/approach : This research uses a comparative, qualitative method. Data were collected from secondary sources, including journals, books, and online literature, and analyzed through collection, classification, and interpretation. Findings : In Indonesia, party switching is driven by “political vehicles,” while in Brazil it is shaped by “physiological parties” and the “party window” mechanism. Indonesia’s electoral threshold influences switching intensity, curbing some practices while enabling legislators to move from smaller to larger parties likely to surpass it—an option absent in Brazil, which has no threshold regulation. Party switching is also linked to the pursuit of political resources: political dynasties in Indonesia and pork barrel politics in Brazil. Practical Implication : Findings can help political parties strengthen internal organization and enhance the role of electoral judicial institutions. Originality/value : This research is original in comparing the causes of party switching between Indonesia and Brazil, differing from prior studies that focus mainly on the reasons behind party switching. Paper type : Research Paper.